Analisis Keterlaksanaan Pembelajaran Fisika Berbasis Inkuiri Terbimbing Dipadu Advance Organizer di SMA - Mahesti Kusdiastuti; Gunawan Gunawan; Ahmad Harjono (Indonesian Journal of Teacher Education, 2021)
This study aimed to analyze the implementation fidelity of guided inquiry-based physics learning integrated with an advance organizer during field testing in senior high schools. As part of the development phase in a 4D research model, this descriptive quantitative study involved tenth-grade students across three public senior high schools in Mataram, Indonesia. Data regarding learning implementation were collected over four instructional sessions using structured observation sheets administered independently by two observers at each school. The observation scores were analyzed descriptively to determine average implementation percentages and inter-observer reliability. The findings revealed a consistent upward trend in learning implementation across all three target schools. Initial sessions (Meetings I and II) demonstrated a "Practical" category with implementation rates ranging from 74.00% to 77.50%, which progressively improved to "Very Practical" during Meetings III and IV, reaching a peak implementation rate of 86.10% (mean score of 4.31) across all groups by the final session. These results confirm that the developed learning package exhibits high implementation fidelity, consistency, and practical applicability in real classroom environments, effectively supporting the systematic delivery of physics instruction.